Study on Vertical Uplift Resistance Characteristics of Pre-Drilled Planted Piles in Boulder Strata - Wenli Liao; Qipeng Cai; Hao Lin; Jiajin Zhou; Shizhuo Su; Xiangyu Guo (Applied Sciences)
Pre-drilled composite planted piles are a commonly used construction method, but there is currently limited research on the load-bearing characteristics of piles penetrating boulders. Therefore, a new type of pre-drilled composite planted pile suitable for sites with isolated boulders has been developed. Using transparent soil technology, vertical uplift bearing capacity tests were conducted on pre-drilled piles to investigate the uplift capacity and load transfer mechanism of piles with boulders. Additionally, a discrete–continuous coupled 3D numerical model was employed to analyze the influence of boulder position on the pile’s uplift bearing capacity. The results indicate that the ultimate uplift bearing capacity of piles with boulders in the pile body is approximately twice that of piles without boulders, and this difference decreases with the increase of the distance between boulder and the pile end; under ultimate uplift loading, the pile end of a pile containing boulders contributes approximately 32% of the uplift bearing capacity, whereas the pile end without boulders contributes almost no uplift capacity; the presence of boulders increases the cross-sectional diameter of the pile, providing additional vertical support from the overlying soil, thereby significantly enhancing the ultimate uplift bearing capacity of the pile. Additionally, the boulder also increases the pathways for load transfer to the surrounding soil, further expanding the impact area on the soil surrounding the piles. Parameter analysis of the position of the boulder in the pile body reveals that under various conditions (boulder distances from the pile tip of 0, 50, 100, and 150 mm), both the ultimate uplift bearing capacity and the angle of the sliding failure surface decrease gradually as the depth of boulder decreases. This study provides a novel solution for pile foundation construction in similar boulder strata.